Toxicological evaluation and polyphenols characterization of pterospartum tridentatum leaf extracts - Ferreira, Fernanda M. (2015)
Pterospartum tridentatum Willk. (prickled broom) is a common autochthonous plant in Portugal. Leaves and stems are normally used in cooking, to flavour rice, roast meat or hunting animals. Leaves are also used as a condiment in fresh salads and, despite of its traditional use, no toxicological evaluation has been performed. P. tridentatum leaves aqueous extract ESI-MS spectrum revealed the presence of several luteolin and isorhamnetin derived phenolic compounds, which can be associated to the health benefits claimed for this plant species. Still, P. tridentatum leaves extract (up to 100 µg plant extract.mg-1 protein) stimulated state 4 and FCCP-stimulated liver mitochondria respiratory rates and inhibited the state 3 respiratory rate. Respiratory control ratio was decreased, indicating a dysfunction in respiratory activity induced by P. tridentatum leaves extract and, in good agreement with the previous results cytotoxicity evaluation by MTT assay (50 and 125 µg plant extract.10-6 cells) showed a decrease on HepG2 cell viability. Overall, the present study suggests that the consumption of P. tridentatum leaves in high amounts or continuously should be regarded as potencially noxious.